Novel Synthesis of 3,4-Diarylisoxazole Analogues of Valdecoxib: Reversal Cyclooxygenase-2 Selectivity by Sulfonamide Group Removal - Di Nunno, Leonardo; Vitale, Paola; Scilimati, Antonio; Tacconelli, Stefania; Patrignani, Paola (Journal of medicinal chemistry, 2004)
3,4-Diarylisoxazole analogues of valdecoxib [4-(5-methyl-3-phenylisoxazol-4-yl)-benzensulfonamide], a selective cyclooxygenase-2 (COX-2) inhibitor, were synthesized by 1,3-dipolar cycloaddition of arylnitrile oxides to the enolate ion of phenylacetone regioselectively prepared in situ with lithium diisopropylamide at 0 °C. The corresponding 3-aryl-5-methyl-4-phenylisoxazoles were easily generated by a dehydration/aromatization reaction under basic conditions of 3-aryl-5-hydroxy-5-methyl-4-phenyl-2-isoxazolines and further transformed into their benzenesulfonamide derivatives. The biochemical COX-1/COX-2 selectivity was evaluated in vitro by using the human whole blood assays of COX isozyme activity. Three compounds not bearing the sulfonamide group present in valdecoxib were selective COX-1 inhibitors.